1986
DOI: 10.1038/321776a0
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an FSH releasing protein from porcine ovarian follicular fluid

Abstract: A variety of hypophysiotropic peptides or proteins have been reported to be present in mammalian gonads. Inhibin, a hormone that under most circumstances selectively suppresses the secretion of follicle-stimulating hormone (FSH) but not luteinizing hormone (LH), has been isolated from the gonadal fluids of several species and characterized as a heterodimeric protein consisting of alpha- and beta-polypeptides associated by disulphide bonds. The complete amino-acid sequences of the precursors of porcine and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
230
0
9

Year Published

1990
1990
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,108 publications
(241 citation statements)
references
References 21 publications
2
230
0
9
Order By: Relevance
“…Several cytokines regulate the proliferation and differentiation of hematopoietic stem cells, Erythroid differentiation factor (EDF), which was isolated from conditioned media of phorbol ester-treated THP-1 cells, has a potent differentiation-inducing activity for murine erythroleukemia (MEL) cells [1]. A subsequent study showed that EDF was identical to activin A that was first purified from ovarian fluid as a factor to stimulate the secretion of pituitary follicular-stimulating hormone [2]. Several reports have shown that activin A can modulate the colony formation of erythroid burst-forming units and erythroid colony-forming units [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Several cytokines regulate the proliferation and differentiation of hematopoietic stem cells, Erythroid differentiation factor (EDF), which was isolated from conditioned media of phorbol ester-treated THP-1 cells, has a potent differentiation-inducing activity for murine erythroleukemia (MEL) cells [1]. A subsequent study showed that EDF was identical to activin A that was first purified from ovarian fluid as a factor to stimulate the secretion of pituitary follicular-stimulating hormone [2]. Several reports have shown that activin A can modulate the colony formation of erythroid burst-forming units and erythroid colony-forming units [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…It was initially recognized as a gonadal protein that stimulates the release of follicular-stimulating hormone (FSH) from the pituitary gland (Vale et al, 1986;Ling et al, 1986). Several studies have shown that activin A carries out a variety of functions including regulation of hematopoiesis (Eto et al, 1987;Yu et al, 1989;Yamashita et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Activin A is highly homologous with transforming growth factor (TGF)-b and consists of two bA subunits (Vale et al, 1986;Ling et al, 1986). It was initially recognized as a gonadal protein that stimulates the release of follicular-stimulating hormone (FSH) from the pituitary gland (Vale et al, 1986;Ling et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Activin A was originally isolated as a factor stimulating secretion of follicle-stimulating hormone (FSH) from anterior pituitary cells [1]. It possesses various in vitro activities such as enhancement of neuronal survival [2], induction of erythroid differentiation [3] and mesoderm formation during amphibian embryonic development [4,5].…”
Section: Introductionmentioning
confidence: 99%